2013
DOI: 10.1155/2013/309831
|View full text |Cite
|
Sign up to set email alerts
|

Integrative TCM Conservative Therapy for Low Back Pain due to Lumbar Disc Herniation: A Randomized Controlled Clinical Trial

Abstract: Low back pain due to lumbar disc herniation (LDH) is very common in clinic. This randomized controlled trial was designed to investigate the effects of integrative TCM conservative therapy for low back pain due to LDH. A total of 408 patients with low back pain due to LDH were randomly assigned to an experimental group with integrative TCM therapy and a control group with normal conservative treatment by the ratio of 3 : 1. The primary outcome was the pain by the visual analogue scale (VAS). The secondary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
8
2
Order By: Relevance
“…Another trial conducted in China demonstrated [26] that the decrease in the mean value of the leg pain intensity NRS score in the EA group was 4.65 ± 6.37 at week 4, which was higher than the value of 2.30 (1.86–2.75) obtained in our trial at the same time point. In a pilot trial comparing EA with physical therapy for symptomatic lumbar spinal stenosis (LSS) [27], pain in the back and leg showed small improvements at 3 months.…”
Section: Discussioncontrasting
confidence: 91%
“…Another trial conducted in China demonstrated [26] that the decrease in the mean value of the leg pain intensity NRS score in the EA group was 4.65 ± 6.37 at week 4, which was higher than the value of 2.30 (1.86–2.75) obtained in our trial at the same time point. In a pilot trial comparing EA with physical therapy for symptomatic lumbar spinal stenosis (LSS) [27], pain in the back and leg showed small improvements at 3 months.…”
Section: Discussioncontrasting
confidence: 91%
“…Some studies have reported the effectiveness of herbal medicine, which is the most popular form of complementary and alternative medical therapy for the treatment of LDH, either used alone or concomitantly with usual care. [ 9 , 15 , 16 ] The limited quality and small sample sizes of the few trials that have been conducted to date have made it difficult to reach firm conclusions about TCM treatments. Well-designed randomized controlled trials are needed to examine the efficacy of TCM treatments for LDH.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, we refer to the literature [ 9 , 15 17 ] and set the inclusion criteria as follows: (1) age 20 to 60 years;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,18,19,20,21] As a treasure of China, TCM has unique advantages in the treatment of some chronic complex diseases. [22,23,24] Shujinjianyao pill (SJJYP) is a kind of Chinese patent medicine containing many kinds of traditional Chinese herbs, which is mainly used to treat low back pain, sciatica, and other diseases in clinic. [25,26,27] However, there is no study that has been conducted on its safety.…”
Section: Introductionmentioning
confidence: 99%